1999
DOI: 10.1016/s0014-5793(99)01224-7
|View full text |Cite
|
Sign up to set email alerts
|

A human homolog of Drosophila warts tumor suppressor, h‐warts, localized to mitotic apparatus and specifically phosphorylated during mitosis

Abstract: We identified a human homolog of Drosophila warts tumor suppressor gene, termed h-warts, which was mapped at chromosome 6q24-25.1. The h-warts protein has a serine/ threonine kinase domain and is localized to centrosomes in interphase cells. However, it becomes localized to the mitotic apparatus, including spindle pole bodies, mitotic spindle, and midbody, in a highly dynamic manner during mitosis. Furthermore, h-warts is specifically phosphorylated in cells at mitotic phase, most likely by Cdc2 kinase. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0
10

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 35 publications
(43 reference statements)
5
90
0
10
Order By: Relevance
“…Of particular interest is Lats1, which shares 52% overall sequence identity with Lats2, with 85% sequence identity over the kinase domain (Yabuta et al 2000). Lats1 also resides on interphase centrosomes (Nishiyama et al 1999;Hirota et al 2000). Indeed, overexpression of kinase-dead Lats1, presumably acting in a dominant-negative fashion, causes prolonged mitotic delay and impairment of the G1 tetraploidy checkpoint as a result of inefficient p53 induction (Iida et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is Lats1, which shares 52% overall sequence identity with Lats2, with 85% sequence identity over the kinase domain (Yabuta et al 2000). Lats1 also resides on interphase centrosomes (Nishiyama et al 1999;Hirota et al 2000). Indeed, overexpression of kinase-dead Lats1, presumably acting in a dominant-negative fashion, causes prolonged mitotic delay and impairment of the G1 tetraploidy checkpoint as a result of inefficient p53 induction (Iida et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, no known Rabs have been shown to be required for mitotic exit or cytokinesis. Interestingly, the kinase domain of Warts/Lats1 exhibits a significant degree of sequence identity to Dbf2 (34%) and localizes to the interphase centrosomes and mitotic midbody (Nishiyama et al, 1999;Tao et al, 1999;Hirota et al, 2000). A conserved nuclear protein kinase Ndr2 (Millward et al, 1995(Millward et al, , 1999 is also closely related to Dbf2 (35% identity).…”
Section: Cytokinesismentioning
confidence: 99%
“…A mammalian homolog of the Drosophila tumorsuppressor protein warts, known as WARTS (or large tumor-suppressor 1 (LATS1)), was identified (Nishiyama et al, 1999;Tao et al, 1999) and found to have functions similar to its activity in Drosophila: mice deficient in WARTS (WTS)/LATS1 develop malignant tumors . WTS encodes a serine-threonine kinase that shares a high degree of sequence homology with members of the myotonic dystrophy protein kinase (DMPK) family, many of which participate in mitotic events.…”
Section: Introductionmentioning
confidence: 99%